2008
DOI: 10.1016/j.rmed.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in airway hyperresponsiveness following smoking cessation: Comparisons between Mch and AMP

Abstract: Smoking cessation can improve AHR in smokers who quit with a 6 months improvement being reported for the airways response to AMP but not Mch. AMP challenge may detect earlier changes in AHR in smokers during smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 39 publications
5
38
1
4
Order By: Relevance
“…As reported by VAN DEN BERGE et al [12], the critical role of inflammatory cells, such as neutrophils, macrophages and lymphocytes, and air trapping in relation to BHR serves as a characterisation tool in the distinction of phenotypes of chronic airway diseases. Prospective studies have shown significant reduction in BHR in asthmatic smokers after quitting; thus smokers should be assisted in quitting [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by VAN DEN BERGE et al [12], the critical role of inflammatory cells, such as neutrophils, macrophages and lymphocytes, and air trapping in relation to BHR serves as a characterisation tool in the distinction of phenotypes of chronic airway diseases. Prospective studies have shown significant reduction in BHR in asthmatic smokers after quitting; thus smokers should be assisted in quitting [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…BHR testing is a common tool in diagnosing asthma, but the effects of smoking have been unclear when interpreting causes of BHR [9]. The association of BHR and smoking has been studied mostly in selected populations [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The smoking-cessation intervention adopted at our clinical research unit has been described previously [13]. At baseline, sociodemographic factors together with a detailed smoking history (number of cigarettes smoked per day, pack-yrs, previous quit attempts and motivation score) were recorded.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…This questionnaire (Appendix 1) evaluates the motivation of a smoker willing to make a quit attempt and consists of 15 items. It classifies motivation to quit according to four possibilities of success: 1) it is not the time to quit (,6), 2) discrete (6-12), 3) good (12)(13)(14)(15)(16), and 4) very good (.16). The GN-SBQ (Appendix 2) consists of 11 items and classifies behavioural dependence according to quartiles: mild (,12), moderate (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), strong (23-33) and very strong (.33).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…At CPCT, smoking cessation programs are based on an adaptation from the Clinical Practice Guideline on Smoking Cessation of the US Department of Health and Human Services [5] and have been described previously in detail [15]. Staff at CPCT includes a dedicated team of clinical psychologists, psychiatrists, physicians, and nurses with at least 3-yr experience.…”
Section: Case Reportmentioning
confidence: 99%